Membrane phospholipid bilayer as a determinant of monoacylglycerol lipase kinetic profile and conformational repertoire. (29th April 2013) - Nasr, Mahmoud L.; Shi, Xiaomeng; Bowman, Anna L.; Johnson, Michael; Zvonok, Nikolai; Janero, David R.; Vemuri, V. Kiran; Wales, Thomas E.; Engen, John R.; Makriyannis, Alexandros
Abstract: The membrane‐associated serine hydrolase, monoacylglycerol lipase (MGL), is a well‐recognized therapeutic target that regulates endocannabinoid signaling. Crystallographic studies, while providing structural information about static MGL states, offer no direct experimental insight into the impact of MGL's membrane association upon its structure–function landscape. We report application of phospholipid bilayer nanodiscs as biomembrane models with which to evaluate the effect of a membrane system on the catalytic properties and conformational dynamics of human MGL (hMGL). Anionic and charge‐neutral phospholipid bilayer nanodiscs enhanced hMGL's kinetic properties [apparent maximum velocity ( V max ) and substrate affinity ( K m )]. Hydrogen exchange mass spectrometry (HX MS) was used as a conformational analysis method to profile experimentally the extent of hMGL–nanodisc interaction and its impact upon hMGL structure. We provide evidence that significant regions of hMGL lid‐domain helix α4 and neighboring helix α6 interact with the nanodisc phospholipid bilayer, anchoring hMGL in a more open conformation to facilitate ligand access to the enzyme's substrate‐binding channel. Covalent modification of membrane‐associated hMGL by the irreversible carbamate inhibitor, AM6580, shielded the active site region, but did not increase solvent exposure of the lid domain, suggesting that the inactive, carbamylated enzyme remains intact and membrane associated. Molecular dynamics simulations generated conformational models congruent with the open, membrane‐associated topology of active and inhibited, covalently‐modified hMGL. Our data indicate that hMGL interaction with a phospholipid membrane bilayer induces regional changes in the enzyme's conformation that favor its recruiting lipophilic substrate/inhibitor from membrane stores to the active site via the lid, resulting in enhanced hMGL catalytic activity and substrate affinity.